Actuation System Design for a Morphing Wing Trailing Edge - Dimino, Ignazio; Flauto, Domenico; Diodati, Gianluca; Concilio, Antonio; Pecora, Rosario (Recent Patents on Mechanical Engineering, 2014)
Shape control of adaptive wings has the potential to improve aircraft aerodynamic performance during cruise. In recent years, several patents have been issued for inventions in the field of morphing wings, using hydraulic, electromechanical or smart material-based actuation concepts and architectures. In the framework of SARISTU project (EUFP7), the joint integration of different conformal morphing concepts in a laminar wing is investigated to improve aircraft performance through a 6% drag reduction, with a positive effect on fuel consumption and required take-off fuel load. An innovative seamless morphing wing incorporating a gapless morphing leading edge, a morphing trailing edge and a wingtip active trailing edge is developed to pursue optimal wing geometry for any flight condition. This paper proposes a state of the art technology to design the actuation system of a morphing trailing edge, consisting of a flexible outer skin and an internal driving mechanism. Focus is given to the modeling and analysis of the morphing actuation, and its integration in the seamless flexible trailing edge control surface. The actuation system is driven by servo rotary actuators and it is designed and established to control the wing trailing edge in order to obtain pre-defined airfoil shapes maximizing wing aerodynamic efficiency. The actuation concept relies on a quick-return mechanism driven by load-bearing actuators controlling the morphing ribs individually. The actuation system is both analytically and numerically addressed. To validate the design, experiments are then carried out with the purpose of estimating the control movement functions suitable for single airfoil camber variations. The morphing rib kinematics including the actuation system is designed to withstand operational pressure loads and actuation forces.
Keywords: numerical modelling